2020
DOI: 10.1016/j.ijscr.2020.10.062
|View full text |Cite
|
Sign up to set email alerts
|

The surgical management of metastatic pancreatic acinar cell carcinoma and associated pancreatic panniculitis—A case report and literature review

Abstract: Highlights Pancreatic acinar cell carcinoma (ACC) may present with pancreatic panniculitis. Complete surgical resection of ACC can successfully treat pancreatic panniculitis. Aggressive surgery for ACC can lead to prolonged disease-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…The cutaneous lesions preceded the diagnosis of underlying neoplastic disease in 48.9% of patients, with a mean lesion-to-diagnosis interval of 134 days. Resection of the tumour can often lead to the complete resolution of pancreatic panniculitis,9 as demonstrated twice in our patient.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The cutaneous lesions preceded the diagnosis of underlying neoplastic disease in 48.9% of patients, with a mean lesion-to-diagnosis interval of 134 days. Resection of the tumour can often lead to the complete resolution of pancreatic panniculitis,9 as demonstrated twice in our patient.…”
Section: Discussionsupporting
confidence: 71%
“…The presenting symptoms are often non-specific and include abdominal and back pain, weight loss, lymphadenopathy and diarrhoea 8. Pancreatic panniculitis, the inflammation of subcutaneous fat associated with pancreatic diseases, is a characteristic feature of acinar cell carcinoma as seen in our case and in several previous reports 9 10. The cutaneous lesions preceded the diagnosis of underlying neoplastic disease in 48.9% of patients, with a mean lesion-to-diagnosis interval of 134 days.…”
Section: Discussionsupporting
confidence: 59%
“…Similar to our study, Landa et al reported 12% of 566 resected PACC patients to be stage IV, with an estimated 5-year survival of 19% versus 4% ( p < 0.001) of not resected stage IV patients [ 5 ]. There have been several case reports of successful curative resections of metastases in PACC [ 24 , 25 , 26 , 27 , 28 , 29 ]. Ohara et al reported the successful resection of metachronous rectal and liver metastases, Kittaki et al and Villano et al performed resections of liver metastases after systemic therapy, and Suzuki et al published a case of a patient with long-term survival after repetitive resection of recurrent liver metastases [ 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%